EFEKTIVITAS SHORTWAVE DIATHERMY DAN NEURODYNAMIC MOBILIZATION PADA RADIKULOPATI LUMBOSAKRAL - Made Hendra Satria Nugraha; Susy Purnawati; Muh. Irfan (Sport and Fitness Journal, 2019)
Radicular syndrome is one type of disease that is included in peripheral nervous system disorders that occur in the spinal roots causing a disturbance of sensory deficits, motor deficits, reflex deficits and damage to pain sensation. In lumbosacral radiculopathy patients, a condition known as fear avoidance belief is a fear to move or to feel pain as a result of doing an activity. This fear of moving causes patients to restrict its movement, so the muscles that should stabilize the inactive vertebral column and the global muscle become hyperactive and trigger muscle spasms. Conservative therapy approaches that may be given to lumbosacral radiculopathy include application of modalities and therapy by physiotherapy, giving modalities of electro physical agents, exercise therapy, and manual therapy interventions. The purpose of this literature review was to determine the effectiveness of intervention shortwave diathermy and neurodynamic mobilization in patients with lumbosacral radiculopathy. The research method used is the study of literature review by using secondary data in the form of study research journals related to the effectiveness of the use of shortwave diathermy and neurodynamic mobilization in patients with lumbosacral radiculopathy. Previous research has shown that the addition of SWD to treat the subjects with chronic back pain complaints can reduce pain. While neurodynamic mobilization is a clinical application to the physiological and mechanical concepts of the nervous system that integrate with the musculoskeletal system. The precise explanation for the improvement of functional disability and pain level experienced by patients with neurodynamic is that neurodynamic may affect the mechanical functioning of peripheral nerves and the change in neural mechanical function have a direct impact on the physiological changes of nerve structure. Based on the literature review, it can be concluded that: the combination of shortwave diathermy and neurodynamic mobilization is effective in improving the limitations of motion and function of lumbosacral radiculopathy patients.